2019
DOI: 10.3892/mmr.2019.10347
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA‑802 increases hepatic oxidative stress and induces insulin resistance in high‑fat fed mice

Abstract: The expression of microRNA-802 (miR-802) is known to be associated with insulin resistance (IR); however, the mechanism remains unclear. The present study investigated how miR-802 contributes to the development of IR using C57BL/6J mice fed a high-fat diet (HFD) to establish a model of IR. Adeno-associated virus overexpressing miR-802 was administered to the mice via tail vein injection. The effects of miR-802 on reactive oxygen species (ROS), lipid peroxidation (LPO) and the activities of multiple ROS-related… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
14
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 31 publications
1
14
0
Order By: Relevance
“…Furthermore, miR-802 induced the expression of phosphorylated p38MAPK and JNK, however, the levels of phospho-ERK remained unchanged. In conclusion, by means of miR-802, HFD may cause IR via activating the JNK and p38MAPK pathways and also suppressing antioxidative enzymes to induce hepatic OxS [ 214 ]. HG-promoted OxS along with IR in HepG2 cells was mediated by decreased levels of miR-233, thus preventing miR-233-dependent direct regulation of Keap1 and reducing levels of Nrf2, HO-1 and SOD1 [ 215 ].…”
Section: Overview Of Mirnas—the Focus On Interplay With Oxidative mentioning
confidence: 99%
“…Furthermore, miR-802 induced the expression of phosphorylated p38MAPK and JNK, however, the levels of phospho-ERK remained unchanged. In conclusion, by means of miR-802, HFD may cause IR via activating the JNK and p38MAPK pathways and also suppressing antioxidative enzymes to induce hepatic OxS [ 214 ]. HG-promoted OxS along with IR in HepG2 cells was mediated by decreased levels of miR-233, thus preventing miR-233-dependent direct regulation of Keap1 and reducing levels of Nrf2, HO-1 and SOD1 [ 215 ].…”
Section: Overview Of Mirnas—the Focus On Interplay With Oxidative mentioning
confidence: 99%
“…As is widely known, the damage occurring in target organs during diabetes is multicausal, so next to high glucose and fatty acids levels, the increased production of reactive oxygen species (ROS) also accounts for the damage. Yang et al [25] demonstrated a connection between miR-802, oxidative stress, and hepatic insulin resistance. In their study, they showed that in HFD mice, miR-802 upregulation was associated not only with higher blood glucose and serum insulin levels but also with a lowered activity of oxidative-stress related enzymes such as SOD (superoxide dismutase), CAT (catalase), and GSH-Px (glutathione peroxidase).…”
Section: Mir-802mentioning
confidence: 99%
“…In one example, the strong induction of lnc7169 by TCPOBOP may contribute to the hepatoprotective effects of CAR activation on high fat diet-induced non-alcoholic fatty liver disease [88,89] by increasing expression of the divergently transcribed Gdf15, a stress response cytokine that is induced by inflammation, acute injury and oxidative stress [58]. In contrast, the very strong induction by TCPOBOP of lnc13509 may stimulate the divergent transcription of miR802, whose expression is elevated in type-II diabetes [64] and in livers of high fat diet-fed mice, where it impairs glucose metabolism and increases oxidative stress [65][66][67]. Alternatively, lnc13509 could serve as hepatoprotective miRNA sponge [90] that depletes miR802, which may be investigated using a variety of experimental and computational approaches [91,92], including innovative knockout technologies [30] that may uncover its biological functions and gene targets in the liver.…”
Section: Discussionmentioning
confidence: 99%
“…We hypothesize that the induction of lnc13509 impacts various biological and pathological responses regulated by miR802. Elevated expression of miR802 is seen in type-II diabetes [64] and in livers of high fat diet-fed mice, where it impairs glucose metabolism by silencing the transcription factor HNF1b and by increasing oxidative stress [65][66][67]. Further, miR802 shows female-biased expression in mouse liver; it preferentially represses many male-biased mRNAs and increases levels of female-biased mRNAs in female liver [68] and has been associated with regulation of glucose and lipid metabolism [67].…”
Section: Differential Enrichment Of Transcripts In Subcellular Fractimentioning
confidence: 99%